Design of Intelligent Fire Extinguishing Vehicle Based on STM32 - Jin, Wei (Scientific Journal of Technology, 2025)
Aiming at the problems of high safety risks for personnel in fire rescue and the lagging response of traditional fire-fighting equipment, this paper designs an intelligent fire-extinguishing trolley control system with the STM32F103C8T6 microcontroller as the core. The system integrates a power supply circuit, motor drive circuit, multi-sensor detection modules (flame, temperature, smoke, obstacle avoidance) and a fire-extinguishing actuator to realize functions such as fire source positioning, automatic obstacle avoidance, sound and light alarm, and desiccant spraying for fire extinguishing. In terms of hardware selection, the L298N chip is used to drive the DC motor to realize the trolley’s motion control; the DS18B20 sensor is used for temperature measurement, the AC4067 infrared sensor for flame detection, the MQ-2 sensor for smoke detection, and the E18-D80NK sensor for obstacle avoidance, ensuring the coordinated and stable operation of each module. Tests show that the trolley can quickly detect the fire source, accurately avoid obstacles, and start fire extinguishing within 10 seconds after locating the fire source, which can effectively improve the efficiency of initial fire handling and reduce the risk of casualties.